The last wish - Sapkowski, Andrzej (Sapkowski, Andrzej. The Witch, 2008)
Geralt de Riv, a witcher, uses his vast sorcerous powers to hunt down the monsters that threaten the world, but he soon discovers that not every monstrous-looking creature is evil, and not everything beautiful is good.